Analisis Kualitas Pelayanan Di Kantor Kelurahan Pasar Baru Kecamatan Sei Tualang Raso Kota Tanjungbalai - Dahlia, Dahlia; Harahap, Dumasari; Lubis, Yurial Arief (Strukturasi: Jurnal Ilmiah Magister Administrasi Publik, 2020)
The results showed that in general the services of the Pasar Baru Village officials did not meet the expectations of the community, where the community still felt weaknesses which had an impact on the interests of the community itself. But overall the quality of service in the Pasar Baru Village Office related to a Building Construction Permit (IMB) can be said to be quite good. In terms of appearance and facilities in serving the community (Tangibles), and assurance or trust can be seen from the safety and comfort of the community in providing services, and empathy for the apparatus who have tried to establish good communication and relationships with the local community. But of course Pasar Baru Village also has obstacles in service at Pasar Baru Village Offices, including: Lack of employees in the field of service and mastery of technology, facilities and infrastructure that are inadequate during service and do not yet have Service Standards, especially correspondence. Therefore, in implementing and improving the quality of service for correspondence, the IMB should be made a change that involves all aspects, in this case the government apparatus in the Kelurahan office plays a role in establishing relations between service users and Kelurahan employees.